2006
DOI: 10.1002/mrc.1772
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state 14N MAS NMR of ammonium ions as a spy to structural insights for ammonium salts

Abstract: The high resolution offered by magic-angle spinning (MAS), when compared to the static condition in solid-state NMR of powders, has been used to full advantage in a (14)N MAS NMR study of some ammonium salts: CH(3)NH(3)Cl, (NH(4))(2)(COO)(2) x H(2)O, (CH(3))(3)(C(6)H(5)CH(2))NCl, (CH(3))(3)(C(6)H(5))NI, [(n-C(4)H(9))(4)N](2)Mo(2)O(7), (NH(4))(2)HPO(4), and NH(4)H(2)PO(4). It is shown that the high-quality (14)N MAS NMR spectra, which can be obtained for these salts, allow determination of the (14)N quadrupole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 16 publications
(44 reference statements)
4
55
0
Order By: Relevance
“…These parameters compared poorly with values calculated from a crystal structure, but after optimization of the atomic positions using DFT (with fixed lattice parameters), the predicted values matched the experimental parameters far more closely, thereby confirming the accuracy of the newly optimized structure. In a further 14 N MAS NMR study of tetraalkylammonium salts, this time with multiple sites and larger C Q values, the importance of the spinning rate was highlighted [114]. A MAS spectrum of trimethylbenzylammonium chloride recorded at a spinning rate of 6 kHz could be fitted accurately with a single site, but at 1 kHz the presence of two distinct sites became clear, and was subsequently confirmed by X-ray diffraction (XRD).…”
Section: Broadband Excitationmentioning
confidence: 95%
“…These parameters compared poorly with values calculated from a crystal structure, but after optimization of the atomic positions using DFT (with fixed lattice parameters), the predicted values matched the experimental parameters far more closely, thereby confirming the accuracy of the newly optimized structure. In a further 14 N MAS NMR study of tetraalkylammonium salts, this time with multiple sites and larger C Q values, the importance of the spinning rate was highlighted [114]. A MAS spectrum of trimethylbenzylammonium chloride recorded at a spinning rate of 6 kHz could be fitted accurately with a single site, but at 1 kHz the presence of two distinct sites became clear, and was subsequently confirmed by X-ray diffraction (XRD).…”
Section: Broadband Excitationmentioning
confidence: 95%
“…In solid-state samples, the large electric quadrupole moment results in spectra having a width of several MHz wide due to the first-order quadrupole interaction. The 14 N MAS study of powdered solids has therefore been reduced to samples with quadrupole coupling constants of C Q $ 1 MHz or less [1][2][3][4][5]. Tycko et al [6][7][8] have demonstrated overtone NMR spectroscopy, where spectra are only influenced by the much smaller second-order quadrupole interaction.…”
Section: Introductionmentioning
confidence: 98%
“…In solid-state, the large quadrupolar moment for this spin-1 nucleus often results in NMR spectra of several MHz wide, with powder samples, due to the first-order quadrupole interaction. The study of 14 N MAS spectra was thus reduced to samples with quadrupolar coupling of C Q $ 1 MHz or less [1][2][3][4][5]. In 1986, Tycko et al [6][7][8], inspired by the work of Bloom and Legros [9], showed that using overtone NMR, the spectra would only be influenced by the much narrower second-order quadrupole interaction.…”
Section: Introductionmentioning
confidence: 98%